BIOLOGICAL NUTRITIONAL VALUE OF ZEOLITE-BASED SOIL ENHANCERS - Ugrinović, Milan (Journal on Processing and Energy in Agriculture, 2021)
A series of greenhouse experiments were conducted in order to determine the biological nutritional value of the substrate mixtures based on newly designed zeolite soil enhancers made to replace an earlier registered commercial enhancer (ZeoPlant™). Lettuce (Lactuca sativa L.) was used as a test species. Plant height, number of leaves, and fresh plant mass were measured. During the preliminary experiments the optimal ratio of enriched zeolites in the peat-based substrate mixtures was verified (about 25% volumetric), as well as usability of Pirotski peat for preparation of substrate mixtures. Enriched zeolites (EZa, EZb, EZc, EZd) were mixed in optimal ratio with Pirotski peat and compared to commercial zeolite-based substrate mixture that was used as a control treatment. The control treatment showed the best results. On the other side the differences between other treatments were not significant, but they indicate that some of the examined soil enhancers have a great potential for application in vegetable seedling production.
Keywords: substrates, zeolites, natural peat, vegetable, seedlings